Anatomopathological Alterations of the Placenta with Preeclampsia: A Systematic Review. - Durán Verdesoto, Carmen Amelia (2024)
The objective of this study was to carry out a systematic review that the amount of anatomopathological alterations in placentas from women who would develop PE would be higher compared to placentas from pregnant women without preeclampsia. In methods, for this systematic review, the keywords (“preeclampsia” and “placenta”) were used, four databases were searched: SciELO, Lilacs, Google Scholar and Elsevier. In the results obtained, it is observed that, of the of the 86 registries identified, 6 were eligible. Other findings that, due to their frequency and maternal and fetal adverse outcomes, are very important: microscopic and macroscopic alterations, firstly, excess fibrin, secondly, abundant syncytial knots. Thirdly, infarctions. Within the macroscopic alterations of the placenta, we found low-weight placentas, and, finally, the evaluation of the methodological certainty of the six articles that entered the SR; they reached a score of >70%, classifying them as “sufficiently reported” articles. In conclusion, we say that the anatomopathological alterations that occur in the placenta lead to a dysfunctional, hypoxic, and ischemic placenta, causing PE and maternal, fetal and neonatal complication.